THE IMPROVEMENT ACTIVITIES AND THE LEARNING RESULT OF SOCIAL SUBJECT WITH COOPERATIVE LEARNING MODEL OF TEAMS GAMES TOURNAMENT TYPE AT THE EIGHT GRADE OF SMP NEGERI 9 METRO - Komarudin Komarudin (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2018)
This research is the classroom action research which purposed to find the model and to know the effectiveness of the cooperative learning model of Teams Games Tournament type in improving activities and the learning result of social subject at the eight grade of SMP Negeri 9 Metro academic year 2016 / 2017. The method which used in this research is Classroom Action Research Model. The subject of this research is the students at the eight grade in SMP Negeri 9 Metro. It is 28 students. The data collecting technique of this research is the observation and test. The observation used to get the data of activity and test used to get the data of the result of students’ learning. The procedure of this research is planning the action, implementation the action, observation / evaluation and the first data analysis (the data reduction, the data explanation and reflection). The final data analysis of this research is tabulation among the cycles. The result of this research shows that first is the students’ learning activity from the first cycle to the second cycle has the improvement up to 12,28%. It was from 60,72% in the first cycle up to 75% in the second cycle. Whereas from the second cycle to the third cycle has improvement up to 10,71%. It was from 75% in the second cycle up to 85,71% in the third cycle. The second is the result of students’ learning has the improvement between the first cycle to the second cycle was 15,45%. It was from 60,71% in the first cycle up to 71,43% in the second cycle. In the second cycle to the third cycle has the improvement up to 16,66%. It was from 71,43% in the first cycle up to 89,29% in the third cycle. Based on the research, it can be concluded that the cooperative learning model with Teams Games Tournament type in Standard Competency of Understanding Activity from Economic Actor in Society have tried out, it can improve the learning activity and the result of students’ learning at the eight grade of SMP Negeri 9 Metro academic year 2016 / 2017. Keywords: Activities, Learning Result, and Teams Games Tournament